Pests and diseases in mangrove reforestation areas at Leganes, Mandurrioa and Dumangas, Iloilo, Philippines. - Uy, Julie Bee (2011.)
Naturally-occuring mangrove plants and reforested species experience pests and disease infestations. Documentation of their occurrence is important for better management an protection, most especially for newly planted ones. Unfortunately, there has been minimal documentation on their occurrence in the mangroves of Iloilo. Thus, this study was conducted to do a prelimiary survey on their occurrence. This study aims to answer the occurrene of various pests and and diseases for better control and management to ensure higher survival rates among other factors. Mangrove leaves were characterized and pests infestation were noted. There were seven symptons of diseases identified and eight pests infestations encountered. Avicennia marina and Sonneratia alba have the common spot symptons while Rhizophora mucronata leaves have blight symptons. In insects infestation , Rhizophora mucronata was commonly damaged by chewing, mining skeletonising and folding insects. In addition, three identified insects here observed, there were the leaf tyre, leaf miners and tide watching moth. The differences in leaf chemistry and adaptations imply the difference in the degree of the attack of pests on the mangrove. Moreover, the dynamic lifestyle of the pests itself cause the uncontrollable commonality of the pests and diseases occuring in different areas. In comparison to other study, salt excretion in leaves of some mangrove species serves as an important defense against fungal attack, reducing the vulnerability to severe disease pressure. Moreover, differential leaf damage has been attributed aslo to leaf chemistry, which is the presence of tannins. Avicennia species have lower content of tannins, exhibit higher damage to foliovores compared to that of Rhzophora species. Thus, lead the species more vulnerable to pests attack. this study will be useful as basis to draw possible management strategies of these pests and diseases in mangrove reforestation areas.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Mangroves -- Plants Pest; Mangroves -- Diseases